1977
DOI: 10.1159/000125804
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation of the Relationship between Cerebral Indices and Learning Abilities

Abstract: Indices of cerebral development were computed for 23 different species in order to assess their capacity to accurately reflect differences in learning ability. The resulting correlations between index values and performance on a variety of tasks strongly suggest that this approach may offer the best type of continuum for the comparative study of learning. It was further suggested that if the index proposed by Jerison were expanded to reflect possible neuronal connections, a more powerful measure might be obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

1982
1982
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 22 publications
3
32
0
Order By: Relevance
“…Examination of the associative learning data of Gossette (1968) and Sasvàri (1985) revealed positive correlations between innovation frequency and learning performance (see Timmermans et al, 2000;Webster and Lefebvre, 2001). Further, the same relationship was found in primates when the captive learning data of Riddell and Corl (1977) was examined in conjunction with the primate innovation data set (see Reader and MacDonald, in press). The aforementioned study by Webster and Lefebvre (2001) of ve avian species revealed a positive across-species relationship between innovation frequency and learning test performance in both the eld and captivity.…”
Section: Species Genera and Order Differencesmentioning
confidence: 72%
“…Examination of the associative learning data of Gossette (1968) and Sasvàri (1985) revealed positive correlations between innovation frequency and learning performance (see Timmermans et al, 2000;Webster and Lefebvre, 2001). Further, the same relationship was found in primates when the captive learning data of Riddell and Corl (1977) was examined in conjunction with the primate innovation data set (see Reader and MacDonald, in press). The aforementioned study by Webster and Lefebvre (2001) of ve avian species revealed a positive across-species relationship between innovation frequency and learning test performance in both the eld and captivity.…”
Section: Species Genera and Order Differencesmentioning
confidence: 72%
“…As mentioned above, many of these species dwell in complex reef environments, such as Carcharhinus amblyrhynchos, C. melanopterus , and Trienodon obesus , and some coastal-oceanic species such as Galeocerdo and Sphyrna are also associated with reefs. This provides evidence that increases in the relative size of the brain and the telencephalon are associated with complex environments in sharks, a situation found in many other vertebrates [Riddell and Corl, 1977;Barton et al, 1995;Huber et al, 1997;Striedter, 2005]. Carcharhiniform sharks also tend to be active hunters that live in a 3-dimensional environment and feed on fishes, cephalopods, and other chondrichthyans [Compagno, 1984a, b;Last and Stevens, 1994;Cortés, 1999].…”
Section: Brain Organization and Cerebellar Variationmentioning
confidence: 98%
“…In contrast, there are large quantitative data sets on brain organization of other vertebrate groups such as teleost fishes, birds, and mammals. Strong correlations have been found between brain patterns and various ecological factors, such as diet and feeding habits in teleosts [Bauchot et al, 1977;Huber and Rylander, 1992;Kotrschal and Palzenberger, 1992;Schellart and Prins, 1993;Huber et al, 1997;Kotrschal et al, 1998] and mammals [Eisenberg and Wilson, 1978;Pirlot and Jolicoeur, 1982;Harvey and Krebs, 1990;Hutcheon et al, 2002], habitat complexity in teleosts [Huber et al, 1997], birds [Riddell and Corl, 1977], and mammals [Barton et al, 1995], and increased sociality and/or cognitive skills in birds [Lefebvre et al, 1998[Lefebvre et al, , 2002 and mammals [Kudo and Dunbar, 2001]. A recent conclusion based on these studies is the recognition of groups of species that share certain common characteristics in the relative development of brain areas; these commonalities are termed 'cerebrotypes' [Clark et al, 2001;Iwaniuk and Hurd, 2005].…”
mentioning
confidence: 99%
“…Comparative psychology is exemplified in the work of such authors as Gossette [1968], Powell [1974], Riddell and co-workers [Riddell and Corl, 1977;Riddell, 1979], Wilson and colleagues , Sasvàri [1985] and Plowright et al [1998]. It has mainly focused on associative learning tests presented to a small number (between 2 and 10) of captive species.…”
Section: Comparative Psychologymentioning
confidence: 99%